A strategy for promoting the use of computers across the curriculum at primary school level: a case study - Heukelman, Delene (Rhodes University, Faculty of Education, Department of Education, 1994)
A growing number of primary schools are acquiring computers, mainly through parent funding. The study concerns the promotion of computer use across the curriculum in primary schools. Teachers need to be trained in the use of computers as a teaching aid in different subjects. A study comparing two periods of training was undertaken. Two model C primary schools, administered by the Department of Education and Culture, with similar profiles of educational computer use, were selected for the purpose. A training course consisting of five sections, where the use of the word processor, spreadsheet and database, both as personal tools and as teaching aids were introduced, was offered. Care was taken to select topics from current syllabi and to demonstrate how these topics could be presented and enhanced by using the computer. The training was presented at school A over a period of 8 months and at school B over a period of 5 weeks. The supporting material and contents of the course were the same for both groups. A comparison between the effectiveness of the two training regimes was made. The researcher's initial perceptions of the teachers' initial low level of computer literacy were confirmed by a questionnaire, responded to by each participant. It would seem that the shorter raining period was more effective in raising the level of computer literacy and that if the training period was longer, the contact time should be increased to maintain support. Neither training period resulted in a significant increase in computer use, either as a personal tool or as a teaching aid. The failure to do so may be ascribed to a number of influences, one of which is the teaching style of individual teachers. Changing the teaching style of an experienced teacher takes time and more effort than was available for either training period.
Keywords: Education, Elementary -- Computer programs; Computers and children; Education, Elementary -- Data processing; Computer-assisted instruction